Simulation of Critical Heat Flux Phenomenon Using a Non-heating Hydrogen Evolving System - Park, Hae-Kyun; Chung, Bum-Jin (Frontiers in Energy Research, 2019)
Pool boiling critical heat flux (CHF) at saturated condition was simulated using the hydrogen at the copper cathode in the aqueous solution of sulfuric-acid. The critical current density (CCD) was observed at the cell potential-current density curve, which is analogous to the CHF at the boiling curve. The CHF values calculated by the gas generation rate at the CCD condition showed large discrepancies with the existing CHF values of water boiling system. Meanwhile, the superficial mechanism triggering the CHF and the CCD showed similar characteristics except the size of bubbles. The variation of bubble departure volume with respect to the current density was similar to that of the water vapor but the bubble volume of the present system was 440 times smaller at CCD condition. The critical heat flux value using the present non-heating experiment was corrected accounting for the bubble volumes and the discrepancy with the water CHF was less than 10%. It is concluded that the water CHF condition can be simulated by the non-heating hydrogen evolving system.